Teachers Emotional Intelligence as a Strategy to Encourage Students' Speaking Confidence and Performance - Melly Tiana; Sari Hidayati (Universitas Islam Negeri Palopo, 2026)
Emotional factors play an important role in students’ participation and performance in English as a Foreign Language (EFL) speaking classrooms. However, the emotional dimension of speaking instruction is often overlooked in teaching practices, particularly in vocational school contexts where students frequently experience low confidence and speaking anxiety. This study aims to explore how teachers’ Emotional Intelligence (EI) is implemented as a pedagogical strategy to encourage students’ speaking confidence and performance. A descriptive qualitative approach was employed in a vocational high school in Indonesia involving three English teachers and six eleventh-grade students. Data were collected through classroom observations, semi-structured interviews, and documentation, and were analyzed using an interactive thematic analysis model. The findings show that teachers applied EI through emotional awareness, emotional regulation, empathetic communication, and supportive feedback. These strategies helped create a supportive and psychologically safe classroom environment that reduced students’ speaking anxiety and encouraged active participation. As a result, students demonstrated greater confidence, improved fluency, and stronger willingness to communicate. This study highlights the importance of Emotional Intelligence as a practical pedagogical competence that supports both students’ emotional well-being and speaking development in EFL classrooms.